Antral Brushings and Biopsies for Gastric Campylobacter pylori: A Comparative Study of a Rapid Urease Test, Culture and Histology - Howard M. Estrin; Medhat O. Hassan; Howard S. Carr; Steven J. Czinn (Canadian Journal of Gastroenterology)
A prospective study was conducted to assess the sensitivity and specificity of diagnostic tests for Campylobacter pylori in 60 unselected patients referred for gastroscopy. Urease testing was performed on samples of gastric mucus obtained by a disposable cytology brush and on gastric mucosal biopsies. The combination of the brush urease test and biopsy urease test had a sensitivity of 78% and a specificity of 96%. The combination of the brush urease test and examination of gastric biopsies for curved bacilli had a sensitivity of 96% and a specificity of 96%. The combination of the brush urease and biopsy urease tests will rapidly identify the majority of patients with C pylori. This test is rapid, easy, sensitive and inexpensive. If a pathologist is available, the addition of histologic review for C pylori in combination with the brush urease test, will identify virtually all patients with C pylori without the need for culturing this fastidious organism.